Design, synthesis, and evaluation of some metal ion complexes of mannich base derived from 2-Mercaptobenzimidazole as potential antimicrobial agents - Sabah, Thuraya Q.; R. Baqer, Shaymaa (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
This study aims to prepare new compounds and investigate them spectroscopically and biologically against selected types of positive and negative bacteria and fungi to demonstrate their biological effectiveness. The prepared ligand combining formaldehyde, indole, sulfa benzamide, and 2-mercapto benzimidazole, a Mannich base ligand (L) was synthesized. The six metal ions including Cobalt (II), Nickel (II), Copper (II), Palladium (II), Platinum (IV), and gold (III) have interacted with the ligand and formed new complexes. Different spectroscopic methods, including C.H.N.S., FTIR, UV- Range visible, 1HNMR, 13CNMR, mass spectra, magnetic moment, and molar conductivity were used to suggest the new geometry of the complexes. The result from the infrared spectrum showed that the ligand behaves as tridentate with all prepared complexes. Conductivity analysis revealed the electrolytic nature of palladium, platinum, and gold ions complexes and non-electrolytes. The antibacterial activity of the compounds that were produced was tested using an agar-well diffusion procedure towards two strains of gram-positive as well as two strains of gram-negative bacteria and fungi (Staphylococcus, Streptococcus, Escherichia coli, Pseudomonas aeruginosa, and Candida albicans) respectively at 0.02M. The standard (∆Eo) and (∆Hfo) of ligand and six complexes were calculated using the program Hyper chem 8.0.7. The research established that complexes are more stable than ligands. Calculated HOMO and LUMO and vibration frequencies using (parametric method 3 (PM3)) to find out the active sites in the ligand showed that they can coordinate and note the extent to which the results of theoretical vibrational frequencies are close to the process when calculating the vibrational frequency of the active aggregates.